2005
DOI: 10.1111/j.1365-2036.2005.02469.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimal change oesophagitis: a disease with characteristic differences to erosive oesophagitis

Abstract: SUMMARYBackground: The majority of gastro-oesophageal reflux disease (GERD) seems to be non-erosive reflux disease. Nonerosive reflux disease includes minimal change oesophagitis (whitish or reddish, oedematous change and erosion that is not regarded as mucosal break) and no endoscopic abnormalities. Aim: To investigate the accurate proportion of those with minimal change oesophagitis and to clarify its characteristics. In addition, we evaluated the effect of famotidine (40 mg/ day) in those with minimal chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 21 publications
3
59
0
2
Order By: Relevance
“…The established LA classification divides GERD state into four grades of A to D, with grade D the most severe, as follows: grade A, a mucosal break 5 mm in length; grade B, a mucosal break > 5 mm in length; grade C, a mucosal break continuous between > 2 folds; grade D, a mucosal break 75% of the esophageal circumference. It has been reported that there is a large number of patients with GERD that is below grade A and labeled as grades N and M (Hoshihara and Hashimoto 2000;Nakamura et al 2005). Grade N is defined as no apparent mucosal changes.…”
Section: Evaluation Of Gerdmentioning
confidence: 99%
See 2 more Smart Citations
“…The established LA classification divides GERD state into four grades of A to D, with grade D the most severe, as follows: grade A, a mucosal break 5 mm in length; grade B, a mucosal break > 5 mm in length; grade C, a mucosal break continuous between > 2 folds; grade D, a mucosal break 75% of the esophageal circumference. It has been reported that there is a large number of patients with GERD that is below grade A and labeled as grades N and M (Hoshihara and Hashimoto 2000;Nakamura et al 2005). Grade N is defined as no apparent mucosal changes.…”
Section: Evaluation Of Gerdmentioning
confidence: 99%
“…Endoscopic examination interpretation based on the established LA classification was used in a randomized trial of medical therapy and surgical anti-reflux therapies to study the long-term asthma outcome (Sontag et al 2003). Although the established LA classification is based on the extent of the apparent erosive mucosal breaks of grades A to D, it does not include grade M, which denotes the non-erosive minimal mucosal change (Kiesslich et al 2004;Nakamura et al 2005) of the "discoloring" type of reflux esophagitis (Hoshihara and Hashimoto 2000;Shimoyama et al 2005). This minimal change is caused by acid contacting the esophageal mucosa; on-demand H 2 receptor blockers (H 2 -blockers), which have less effect of acid suppression than PPIs, were reported to be suitable for treating minimal change in GERD (Nakamura et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Minimal change esophagitis was defined as the presence of one of the following characteristics at the distal end of the esophageal mucosa: whitish change and/or erythema, and/or erosion not regarded as mucosal break. 5,6 Patients were also required to be aged 20 years or older, and to be outpatients at the relevant center.…”
Section: Design and Participantsmentioning
confidence: 99%
“…[2][3][4][5][6] Minimal change esophagitis is determined by a characteristic appearance of the distal end of the esophageal mucosa that includes a whitish appearance and/or erythema, and/or erosion that is not regarded as a mucosal break. 5,6 A previous study that included 25,536 individuals who underwent upper gastrointestinal endoscopic examinations as a health check-up showed that minimal change esophagitis was closely related with reflux symptoms including heartburn and acid regurgitation. 3 Minimal change esophagitis, however, was also associated with dyspeptic symptoms including globus sensation and epigastric soreness.…”
Section: Introductionmentioning
confidence: 99%